Analysis Method of Volatile Sulfur Compounds Utilizing Separation Column and Metal Oxide Semiconductor Gas Sensor - Kim, Han Soo; Kim, Inho; Park, Eun Duck; Han, Sang Do (Journal of Sensor Science and Technology, 2024)
Gas chromatography (GC) separation technology and metal oxide semiconductor (MOS) gas sensors have been integrated for the effective analysis of volatile sulfur compounds (VSCs) such as H2S, CH3SH, (CH3)2S, and (CH3)2S2. The separation and detection characteristics of the GC/MOS system using diluted standard gases were investigated for the qualitative and quantitative analysis of VSCs. The typical concentrations of the standard gases were 0.1, 0.5, 1.0, 5.0, and 10.0 ppm. The GC/MOS system successfully separated H2S, CH3SH, (CH3)2S, and (CH3)2S2 using a celite-filled column. The reproducibility of the retention time measurements was at a 3% relative standard deviation level, and the correlation coefficient (R2) for the VSC concentration was greater than 0.99. In addition, the chromatograms of single and mixed gases were almost identical.
Keywords: Column separation; Gas sensor; GC/MOS system; Metal oxide semiconductor (MOS); Volatile sulfur compounds (VSCs)